Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
((x^2)(y^2) - 9) *(3 - xy).
Note difference of two squares: (a^2 - b^2) = (a-b)(a+b)
(x^2)(y^2) - 9 = (xy)^2 - 3 ^2 = (xy - 3)(xy + 3). (Take note)
(3- xy) = -(xy - 3). (Take note of this also)
Your question said: ((x^2)(y^2) - 9) times (3 - xy),
Don't you think it should be divide? Would solve it as divide.
((x^2)(y^2) - 9) /(3 - xy) = (xy - 3)(xy + 3) / -(xy - 3)
= -(xy + 3).
Answer is (3). Solved it as divide. Using times gives none of the solution among the options.
Cheers.
Note difference of two squares: (a^2 - b^2) = (a-b)(a+b)
(x^2)(y^2) - 9 = (xy)^2 - 3 ^2 = (xy - 3)(xy + 3). (Take note)
(3- xy) = -(xy - 3). (Take note of this also)
Your question said: ((x^2)(y^2) - 9) times (3 - xy),
Don't you think it should be divide? Would solve it as divide.
((x^2)(y^2) - 9) /(3 - xy) = (xy - 3)(xy + 3) / -(xy - 3)
= -(xy + 3).
Answer is (3). Solved it as divide. Using times gives none of the solution among the options.
Cheers.
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.